Locoregional Tumor Therapy (Springer International Publishing, 2018)
This book presents, in condensed form, the clinical results achieved by means of various locoregional tumor therapies employed for different indications. In so doing, it will allow the reader to rapidly retrieve the information on indications and effectiveness that is required for optimal integration of these highly effective therapies into modern, complex treatment strategies. The renaissance in locoregional tumor therapies is an ongoing process. New chemotherapeutic schedules, especially for liver and lung tumors, have been developed during the past few years. Other targeted therapies, such as radioembolization, microwave ablation, and HIFU techniques, and new pharmaceuticals for intra-arterial therapy have been developed and implemented in clinical practice. Furthermore, the advantages of unlimited combination of starch microspheres with various antitumor agents, supported by effective ischemia, have been increasingly exploited. The second edition of this book reflects these advances and includes entirely new chapters on the role of intraperitoneal perfusion in treating peritoneal carcinomatosis and the use of limb perfusion. Locoregional Tumor Therapy will be invaluable for all practitioners who work with cancer patients. .